1997
DOI: 10.1016/s0092-8674(01)80009-x
|View full text |Cite
|
Sign up to set email alerts
|

Components and Dynamics of DNA Replication Complexes in S. cerevisiae: Redistribution of MCM Proteins and Cdc45p during S Phase

Abstract: In S. cerevisiae, the chromatin structure of DNA replication origins changes as cells become competent for DNA replication, suggesting that G1 phase-specific association of replication factors with origin DNA regulates entry into S phase. We demonstrate that ORC, Cdc45p, and MCM proteins are components of prereplication complexes (pre-RC). The MCM-origin association is dependent upon ORC and Cdc6p. During S phase, MCM proteins and Cdc45p dissociate from origin DNA and associate with nonorigin DNA with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
784
3
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(845 citation statements)
references
References 48 publications
51
784
3
7
Order By: Relevance
“…As cells progressed into S-phase the association of Mcm2 with the origin decreased and the association of Mcm2p with origin-distal DNA fragments increased. This pattern implies association with the replication fork, as has been previously described (Aparicio et al, 1997;Tanaka et al, 1997). We found that when TetO 7 -SMC4 was shut off, Mcm2p binding to ARS1 decreased as cells progressed into S phase, but Mcm2p failed to then associate with origin-distal regions.…”
Section: S Phasesupporting
confidence: 84%
“…As cells progressed into S-phase the association of Mcm2 with the origin decreased and the association of Mcm2p with origin-distal DNA fragments increased. This pattern implies association with the replication fork, as has been previously described (Aparicio et al, 1997;Tanaka et al, 1997). We found that when TetO 7 -SMC4 was shut off, Mcm2p binding to ARS1 decreased as cells progressed into S phase, but Mcm2p failed to then associate with origin-distal regions.…”
Section: S Phasesupporting
confidence: 84%
“…Orc1 protein was tagged by 3ϫ HA epitope tag cassette at its C terminus using the plasmid p306ORC1-HA/C (18). An ⌬ume6 mutant is a deletion mutant that is constructed by insertion of the KanMX cassette (19).…”
Section: Methodsmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, but also in many other organisms, the binding of Cdc6 to the origin recognition complex (ORC) is a critical step in the formation of pre-RCs (Liang et al, 1995;Cocker et al, 1996;Detweiler and Li, 1997) and essential for subsequent loading of Mcm proteins (Mcm2-7; Piatti et al, 1996;Santocanale and Diffley, 1996;Aparicio et al, 1997;Donovan et al, 1997;Tanaka et al, 1997). After licensing the origin by loading Mcms, endogenous Cdc6 dissociates from the replicative complex and only reassociates with chromatin late in M-phase Weinreich et al, 1999) when cyclin-dependent protein kinase (Clb-Cdc28) activities are absent.…”
Section: Introductionmentioning
confidence: 99%